Fabrication of biogenic-silver nanoparticles functionalized electrospun membranes counteracting bacteria and enhance wound healing. (June 2022) - Ahmad, Fiaz; Ashraf, Noreen; Elahi, Muhammad Inam; Zhou, Yaqing; Lu, Yandu; Yin, Da-Chuan
Abstract: Silver is a non-renewable precious metal with many applications in biomedicine. In this study, we reported fabrication of biogenic-silver nanoparticles (b-AgNPs) functionalized bactericidal membranes with wound healing (WH) activity by near filed electrospinning (NFES). Polycaprolactone (PCL) with or without polyethylene glycol (PEG) and(or) b-AgNPs were used as materials to fabricate membranes of different compositions and geometric shapes. Membranes were functionalized with b-AgNPs by using two methods; 1) combined dissolved, and 2) surface coating. The fabricated membranes were characterized by optical microscope, 2D/3D digital microscope, SEM, EDS, FTIR, and XRD. Water holding potential, water vapor transmission rate (WVTR), and membrane surface roughness were also characterized. Results revealed that the method of membrane functionalization with b-AgNPs and the addition of polyethylene glycol (PEG) has significantly affected bactericidal and WH activity of the membranes. The b-AgNPs functionalized membranes Mem-F and Mem-E showed bactericidal effects with 100% and 70% WH activity, respectively. The calcein-AM/PI staining of C2C12 cells, their adhesion and proliferation on the surface of MEM-F functionalized with b-AgNPs confirmed its non-cytotoxic effects on C2C12 cells. Histological results showed that Mem-F has significantly enhanced cell proliferation and differentiation resulting in fast WH in SD-rats. In conclusion, b-AgNPs functionalized electrospun PCL membranes could be a potential candidate for their use as antibacterial as well as wound dressing material. Graphical Abstract: ga1 Highlights: PCL polymer-based electrospun membranes were functionalized with b-AgNPs. PEG has enhanced adhesion of b-AgNPs and water-holding capacity of membranes. Methods of attributing b-AgNPs to membranes affect bactericidal and WH activity. Membranes functionalized with b-AgNPs were bactericidal with WH potential. Mem-F exhibited 100% WH potential and non-cytotoxic effects on mouse myoblast C2C12 cells.